Pelaksanaan Asesmen Karakter Disiplin Anak Usia 5-6 Tahun Melalui Catatan Anekdot di TK Kasih Bapa Percut - Devi Kristina Tambunan; Artha Mahindra Diputera (Veritas: Jurnal Penalaran dan Riset Mahasiswa Pendidikan, 2026)
This study aims to describe the implementation of discipline character assessment in children aged 5–6 years through anecdotal records and to identify the supporting and inhibiting factors at TK Kasih Bapa Percut. This research employed a qualitative approach with a case study method. The subjects of the study were two teachers of Group B (aged 5–6 years), while the object of the study was the implementation of discipline character assessment through anecdotal records. Data were collected through interviews and documentation. Interviews were conducted with teachers to obtain information regarding the implementation of discipline character assessment, while documentation was carried out by examining anecdotal records used by teachers in recording children’s behavior. Data were analyzed through data reduction, data display, and conclusion drawing. The results showed that discipline character assessment had been integrated into the learning process through lesson planning (RPPH). Teachers assessed children’s discipline through direct observation during learning activities and documented important events using anecdotal records. The assessment was conducted continuously by considering changes in children’s behavior over time, and the results were used as the basis for preparing developmental reports. Supporting factors included teachers’ experience, the use of systematic instruments, and conducive classroom conditions. Meanwhile, inhibiting factors included limited time, a large number of children, and difficulties in maintaining objectivity in recording. Thus, the implementation of discipline character assessment through anecdotal records has been carried out in an integrated and continuous manner and is able to provide a contextual picture of children’s discipline development.